2019
DOI: 10.1055/a-1046-1022
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic Microbiota Comparison of Dendrobium huoshanense Root and Stem in Different Growth Years

Abstract: The endophytic microbiome in medicinal plants is rich and diverse, but few studies have followed the endophytic microbiome of medicinal plants in different tissues with their growth. In this study, we examined the endophytic bacterial and fungal community structures associated with both the stem and root compartments of Dendrobium huoshanense at different growth years via high-throughput sequencing of 16S rRNA genes and nrDNA fragments of internal transcribed spacer regions. Results indicated that more diverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 28 publications
(30 reference statements)
1
20
0
Order By: Relevance
“…In this study, the endophytic fungi associated with the root, stem and leaf tissues of three-yearold H. serrata were characterized and compared. Alpha diversity analysis (Chao1, Ace, Shannon, Simpson) indicated that richness and diversity of endophytic fungi in the H. serrata root samples were lowest (Table 1), which were different from those of the D. huoshanense roots [22], that have a higher richness and diversity of endophytic fungi. A total of 555 fungal OTUs were detected from the three tissue samples of H. serrata, and were further classified into 7 phyla, 21 classes, 50 orders, 95 families and 120 genera.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In this study, the endophytic fungi associated with the root, stem and leaf tissues of three-yearold H. serrata were characterized and compared. Alpha diversity analysis (Chao1, Ace, Shannon, Simpson) indicated that richness and diversity of endophytic fungi in the H. serrata root samples were lowest (Table 1), which were different from those of the D. huoshanense roots [22], that have a higher richness and diversity of endophytic fungi. A total of 555 fungal OTUs were detected from the three tissue samples of H. serrata, and were further classified into 7 phyla, 21 classes, 50 orders, 95 families and 120 genera.…”
Section: Discussionmentioning
confidence: 96%
“…Lee et al used highthroughput sequencing technology to reveal diversity of endophytic bacterial, archaeal and fungal communities inhabiting different rhizocompartments of tomato plants in real-world environments [21]. Chen et al used high-throughput sequencing technology to analyze and compare the endophytic fungal community structures associated with stems and roots of Dendrobium huoshanense [22]. However, few researches on the diversity and composition of endophytes in H. serrata based on high-throughput sequencing have been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…The wild D. huoshanense is often epiphytic to rocks and tree trunks under forest at an altitude of 200–1,200 m ( Yuan et al, 2018 ; Chen et al, 2020 ), can grow well on wet stone walls facing northwest and northeast or cliff stones with waterfalls, and often forms small communities with mosses and lichens ( Chen et al, 2020 ). Due to the unique growth environment, slow growth rates, and excessive manual collection, the wild resources of D. huoshanense are seriously threatened and cannot meet market demand ( Jin et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Modern pharmacological research has revealed that D. huoshanense has anti-inflammatory ( Ge et al, 2018 ; Li et al, 2020 ), cytotoxic ( Chen et al, 2022 ), hypoglycemic ( Wang et al, 2019 ), anti-atherosclerosis ( Fan et al, 2020 ), and antioxidant ( Tian et al, 2013 ) activity. Dendrobium plant is well-known for its rich and diverse endophytic bacterial and fungal community ( Chen et al, 2019 ; Chen et al, 2020 ). Previous studies have revealed the close relationship between Dendrobium and its endophytes, such as improving the seed germination rate ( Tsavkelova et al, 2007 ) and supply of nutrients ( Li et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…At present, research on D. huoshanense endophytes mainly focuses on the diversity and functions, while not much is known about their secondary metabolites, especially for bacteria. The main species of bacterial microorganisms of D. huoshanense are Sphingomonas, Acinetobacter, Enterococcus, Bacillus , and Methylobacterium ( Chen et al, 2020 ). Streptomyces is the largest genus of Actinobacteria and characterized by producing complex secondary metabolites.…”
Section: Introductionmentioning
confidence: 99%